Fundamentals of Futures and Options Markets (4th Edition) - Hull, John C. (Prentice Hall, 2012)
For undergraduate courses in options and futures.This introduction to futures and options markets is ideal for those with limited background in mathematics. Based on Hull's Options, Futures and Other Derivatives, one of the best-selling books on Wall Street and in the college market, this text offers an accessible presentation of the topic without the use of calculus.